Spatial and seasonal variations of atmospheric BTEX, sulfur dioxide, nitrogen dioxide, and ozone concentrations in Istanbul, and health risk assessment of BTEX. Issue 2 (3rd April 2019) - Ercan, Özgen; Dinçer, Faruk; Ceylan, Özcan
Abstract: Volatile organic compounds (VOCs) such as benzene, toluene, ethylbenzene, and xylene (BTEX) along with inorganic gases such as sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), and ozone (O3 ) levels were found in the atmosphere of the Kemerburgaz region where environmental issues became a major concern due to nearby incineration plant and waste disposal facility in Istanbul. Ten sampling locations were selected considering possible sources in the study area. The sampling areas were classified as suburban, industrial, rural, and background regions. Sampling campaigns were carried out for four-week periods from March 2011 to August 2012 in all locations. Elevated concentrations of BTEX around roads and the industrial locations indicated that vehicle exhaust and industrial activities were the main sources of these pollutants in the region. Concentrations of NO2 were also high around roads. A much more uniform distribution was observed for SO2 during sampling periods. However higher levels were observed at suburban locations due to the use of coal for local heating especially during winter. Ozone concentrations were low at the industrial locations and roadsides, but high in suburban and rural locations downwind from the sources. The results of these organic and inorganic gases meet the national limit values. Furthermore, a lifetime risk assessment methodology was used to evaluate the potential adverse health effects of BTEX. The mean cancer risk level for benzene was estimated to be 7.71E-07 that is lower than assigned acceptable risk level of 1.0E-04. Toluene, ethylbenzene, and xylenes were lower than the specified level of 1.0 with respect to mean non-carcinogenic risks. The findings reveal that determined BTEX emissions do not pose a health threat to residents in the studied region.